(untitled) (Research, Society and Development, 2019)
For the accomplishment of this bibliographical research was estimated a range of information that, when entering the main subject of the theme that has as an objective to explain the problems and the effects in which the accidents more specifically the falls in construction sites leads to all involved whether from the responsible for the work to the governmental institutions, to propose the appropriate solutions to this problem that has led to an increase in the statistical numbers of fatal accidents involving these, being they the conscience with their own life and others who in accordance with the rules that, through other studies carried out by employees and placed in standards, dictate certain technical recommendations in which all involved are part, having a notion of the risks involved in their day-to-day work and the appropriate qualifications and prepare them to exercise them.